2009
DOI: 10.1152/ajpgi.00462.2007
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin attenuates angiotensin II-induced inflammatory actions in the liver

Abstract: Statins exert beneficial effects in chronically damaged tissues. Angiotensin II (ANG II) participates in liver fibrogenesis by inducing oxidative stress, inflammation, and transforming growth factor-beta1 (TGF-beta1) expression. We investigate whether atorvastatin modulates ANG II-induced pathogenic effects in the liver. Male Wistar rats were infused with saline or ANG II (100 ng kg(-1) min(-1)) for 4 wk through a subcutaneous osmotic pump. Rats received either vehicle or atorvastatin (5 mg kg(-1) day(-1)) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 51 publications
3
57
0
1
Order By: Relevance
“…20,39,40 Furthermore, others have shown that AngII exposure leads to the recruitment of fibrocytes into renal tissue in a model of kidney fibrosis. 40 Importantly, fibrocytes can be recruited in response to SDF-1a gradients.…”
Section: Discussionmentioning
confidence: 99%
“…20,39,40 Furthermore, others have shown that AngII exposure leads to the recruitment of fibrocytes into renal tissue in a model of kidney fibrosis. 40 Importantly, fibrocytes can be recruited in response to SDF-1a gradients.…”
Section: Discussionmentioning
confidence: 99%
“…TGFb1 synthesis is stimulated by physical, mechanical, and biochemical factors [12]. Increased TGFb1 activity has been observed in response to angiotensin II [13][14][15][16], LDL, glucose, thromboxane A2. Natural inhibitors of TGFb1 are follistatin, decorin, and a2-macroglobulin [12].…”
Section: Tgfb1 and Its Receptorsmentioning
confidence: 99%
“…In chronic processes, the excessive and persistent production of TGFb1 occurs which leads to progressive fibrosis [7,47,48,68]. Synthesis and profibrogenic action of TGFb1 are intensified by angiotensin II which is therefore another mediator of ECM production in the liver [13,[14][15][16]. TGFb1 is one of the key mediators of fibrogenesis.…”
Section: Prace Poglądowementioning
confidence: 99%
“…40,41 Several data suggested the involvement of TNF-α and IL-6 in the metabolic syndrome and progression of NAFLD, perhaps, in part through increased mitochondrial dysfunction and 44 Ang II-infused rats presented increased IL-6 expression in the liver with associated increase in monocyte recruitment and overall inflammation. 45 A recent study showed that Ang-(1-7) was able to reduce inflammatory markers in rats with diabetic nephropathy. 46 These data were supported by a study that revealed different molecular approaches for Ang-(1-7)-modulated inflammatory responses in mouse peritoneal macrophages, decreasing IL-6 and TNF-α.…”
mentioning
confidence: 99%